ACETAMIPRID INDUCED CHANGES IN TOTAL LEUCOCYTES AL LEUCOCYTES AND ERYTHROCYTES COUNT IN A FRESHWATER FISH, CHANNA PUNCTATUS (BLOCH) (BLOCH) - M. S. SIDDIQUI; D. D. WANULE (The Bioscan, 2010)
Inspite of adverse effects of insecticides and insecticides on the living beings, we are constantly using these biohazardous chemicals. In the present investigation, acetamiprid has been used to study its comparative effects of different sub-lethal concentrations on total leucocytes and erythrocyes count in a fresh water fish Channa puntatus (Bloch).